GAMBARAN KASUS HIPERTENSI DI WILAYAH KERJA PUSKESMAS LABOY JAYA - Arif, Muhajir; Hanafi, Ahmad; Kurniati, Rizki (Ensiklopedia of Journal, 2024)
Hypertension is a major risk factor for cardiovascular diseases and the leading cause of death in Indonesia. There are several factors that can cause hypertension and these factors can be changed such as excessive salt consumption, alcohol consumption, smoking, obesity and factors that cannot be changed such as gender, age and genetics. Based on document searches, it is known that hypertension cases are non-communicable diseases with the highest cases. In 2022 hypertension cases amounted to 1374 cases and in 2023 there was an increase of 2233 cases. The research method uses descriptive quantitative research using secondary data in the form of hypertension case reports at the Laboy Jaya Health Center in 2021-2023 by looking at the number of cases by year and gender. The results showed that for 3 years, the number of hypertension cases has increased in the Laboy Jaya Health Center working area. Meanwhile, according to gender, women tend to experience more hypertension than men.Keywords: Hypertension, Gender, Health Center